Mould counts in the atmosphere at the Europe quarter of Istanbul, Turkey - ÇOLAKOĞLU, GÜNAY TÜLAY (WILEY, 1996)
Daily mould counts were made using both exposed slides and Petri dishes, from January 1, 1994 to December 31, 1994 in Europe Quarter of Istanbul, Turkey. The most important moulds were: Cladosporium, Alternaria, Penicillium, Aspergillus and yeast. The peak mould season was early January to early February. Some moulds were present all year.
Keywords: ASTHMA; ALLERGENS